2002
DOI: 10.1144/gsl.sp.2002.194.01.04
|View full text |Cite
|
Sign up to set email alerts
|

Diversification and biogeography of bivalves during the Ordovician Period

Abstract: Bivalves have a wide distribution in the Lower and to a lesser extent Middle Cambrian rocks, but they have not yet been certainly identified in the Upper Cambrian. Recent discoveries have significantly increased our knowledge of Lower Ordovician bivalve faunas and their explosive radiation from the Early Ordovician apparently coincides with the evolution of the feeding gill. Early Ordovician faunas were confined to the siliciclastic facies of Gondwanan shelf seas; most genera were clearly latitudinally constra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(88 citation statements)
references
References 29 publications
3
81
4
Order By: Relevance
“…Of further note is that the dominance of higher taxa during the Tremadocian-lower Darriwilian interval of both the NWA and Famatina basins deviates from patterns recognized in previous studies (e.g. Cope & Babin 1999, Babin 2000.…”
contrasting
confidence: 69%
“…Of further note is that the dominance of higher taxa during the Tremadocian-lower Darriwilian interval of both the NWA and Famatina basins deviates from patterns recognized in previous studies (e.g. Cope & Babin 1999, Babin 2000.…”
contrasting
confidence: 69%
“…runnegar and benTley (1983) suggested that Pojetaia and Fordilla were anatomically like a young Nucula; but in Fang's (2006a) opinion, they were at a proto-palpal evolutionary stage. In any case, it is improper to place Pojetaia and Fordilla in Nuculoida (Protobranchia) (runnegar & PojeTa, 1992;coPe, 1997;geyer & sTreng, 1998;coPe & babin, 1999;hinZschallreuTer, 2000), because they probably lacked palp proboscides, which are unique to Protobranchia (Waller, 1998), as well as paleotaxodont hinge teeth, which are characteristic of the earliest Protobranchia (carTer, caMPbell, & caMPbell, 2000).…”
Section: Life Habits Of Cambrian Archetype Bivalvesmentioning
confidence: 99%
“…It has long been acknowledged that the Ordovician is characterized by two diversification peaks, one in the early Ordovician and another in the late Ordovician (e.g., babin, 1993Ordovician (e.g., babin, , 1995Ordovician (e.g., babin, , 2001coPe & babin, 1999;coPe, 2002coPe, , 2004. The first one is recorded mainly on the clastic platforms of northwestern Gondwana and peripheral microplates, whereas the second one is recorded mainly in carbonate and mixed platforms located at mid-to low-paleolatitudes in Laurentia, Baltica, Siberia, and Kazakhstan.…”
Section: Ordovician Radiation Of Crown-group Bivalvesmentioning
confidence: 99%
See 2 more Smart Citations